(untitled) (Bangladesh Journal of Pharmacology, 2016)
Diazotization of substituted anilines with NaNO2 and concentrated hydrochloric acid at 0ºC gave the diazonium chlorides. Coupling of substituted aryl diazonium chlorides with ethyl acetoacetate in methanol gave ethyl-2-aryl-hydrazono-3-oxobutyrates (2a-h). Reaction of (2a-h) with naphthoic carbohydrazide (3) gave the title compounds pyrazolone derivatives (4a-h). The newly synthesized compounds were screened for their in vivo anti-depressant activity by tail suspension test and forced swimming test. Some of the tested compounds 4f, 4g showed very good activity when compared to the standard drug imipramine. The newly synthesized compounds were characterized by physical parameters and the structures were elucidated by spectral data. Video Clips of Methodology: Forced swimming test: 12 min 19 sec Full Screen Alternate Tail suspension test: 8 min 5 sec Full Screen Alternate